TINJAUAN SISTEMATIS INSTAGRAM SEBAGAI ALAT UNTUK ELT - fauzi, Rafi Ahmad Fauzi; Muhammad Ali Isa Pena; Nafan Tarihoran (PT. Intelek Cendikiawan Nusantara, 2025)
Through an analysis of 18 articles published between 2015 and 2023, this systematic review investigates Instagram's use in English language teaching (ELT). It emphasizes how Instagram improves writing skills, aids identity formation, stimulates student interest, and promotes socially conscious teaching. Results indicate that Instagram provides a forum for reflective learning, boosts motivation, and enables genuine conversation. While it encourages individual and group expression, it also presents difficulties for digital literacy and instructional design. According to the review, when used pedagogically, Instagram can be a useful tool in contemporary ELT courses. ​